Social Choice Theory: A Re-Examination - Sen, Amartya (Econometrica, 1977)
Recent developments in social theory are critically surveyed in the light of a categorization of interpersonal aggregation problems into four distinct types that seem to require varying treatment but typically do not receive it. Informational inadequacy of the usual social framework is discussed in this context. A fairly thorough exploration of the correspondences between consistency conditions for functions and regularity properties of the binary relation of preference leads to a re-examination of the class of impossibility results in social theory, necessitating reinterpretations of various theorems (including Arrow's). SOCIAL CHOICE THEORY is concerned with relationships between individuals' preferences and social choice (Fishburn (1973, p. 3)). But a great many problems fit this general description and they can be classified into types that are fundamentally different from each other. It can be argued that some of the difficulties in the general theory of social arise from a desire to fit essentially different classes of group aggregation problems into one uniform framework and from seeking excessive generality. An alternative is to classify these problems into a number of categories and to investigate the appropriate structure for each category. In a small way, this is what will be done in this paper, and some of the recent developments in the theory of social will be examined in that light.